PELATIHAN PENGENALAN INVESTASI SAHAM PADA WARGA KELURAHAN PLAMONGANSARI, KECAMATAN PEDURUNGAN KOTA SEMARANG SEBAGAI ALTERNATIF PASSIVE INCOME - Patricia Dhiana Paramita; Cicik Harini (Majalah Ilmiah Inspiratif, 2022)
Passive income is an income that continues to grow when you are no longer doing business, such as quitting your job, or when your investment capital has returned. If passive income is managed properly, it will be able to become another source of income besides active income every month that is obtained from working or doing other productive businesses. Starting from the desire to invite residents to optimize passive income, the Pandanaran University Community Service team took the initiative to hold training on the introduction of stock investment as an alternative to passive income.So far,based  on  the  observations  of  the  residents of  Plamongansari Village, active   income  has  been  prioritized  and   put  aside  passive  income,  even  though investing in shares will bring benefits that can have a  positive  impact  on  improving people's  living  standards.  Socialization  about passive income with stock investment has never  been  done  in  Plamongansari Village. This is motivated by the absence of competent  people  in  the  field  of  stock  investment  who  provide  introduction  and training  to  the  residents  of  Plamongansari  Village,  which   aims  to   increase  the residents'   passive  income, thus  requiring  a  continuous socialization, training  and mentoring program regarding stock investment.Through   a   program  of   socialization,  training  and   mentoring   on  stock investment  and  capital   markets   for  residents, it  is  expected  that  citizens  will  change  their mindside  to  manage  passive  income  by   investing  in  stocks. There  is  a need  for cooperation with relevant agencie to provide socialization,counseling  and assistance to residents of Plamongansari Village,such as from IDX (Indonesia Stock Exchange), securities companies and  OJK (Financial Services Authority) in  terms  of  providing  regular and  continuous  training  on  how to  do  profitable  and  minimal  risk  stock investment and how to trade on the national stock exchange market. Keywords: passive income, stock investment